Experiences of Innovation Projects in the Light of the „European Paradox” - Tóthné Kiss, Anett (International Journal of Engineering and Management Sciences, 2017)
Corporate innovation can be a major factor in economic development and long-term high-level corporate performance. The position of the EU in international innovation rankings has not improved since the 2000 2009 period; though there has been a more positive trend since 2010, meeting the Lisbon goals, the EU is still not at the forefront in terms of R&D&I. Behind this process is the rapid progress of some industrially developing nations in R&D&I, as well as the relatively slow institutional development of national innovation systems in Europe. The relative lag in Europe can be explained by the frequently referred to “European paradox”, which is still unclear for methodological reasons. Firstly we consider the international ranking in innovation, then discuss one of the explanations put forth to explain this rather weak performance. We present case study that represent Hungarian experiences with corporate innovation.